Democratization of authority in public universities in Poland in the context of the act on higher education and science - Kilanowski , Igor M. (Prawo Kanoniczne, 2024)
The article analyzes the process of democratization of power in Polish public universities in light of the Act of July 20, 2018 – Law on Higher Education and Science (the so-called “Constitution for Science”). The starting point is a comparison of the current solutions with those in force under the previous regulation of 2005. After emphasizing that collegiality and academic self-government are a tradition in Polish higher education, the author analyzes the applicable legal norms, providing commentary and his own observations related to the practical application of the provisions of the Act in everyday life. Three statutory and key university bodies are discussed: the senate, the university council, and the rector, and the method of selecting these bodies is also presented. The study identifies proposals related to the amendment of the provisions of the Act, as well as reflections on the need to find a balance between centralized management (which promotes efficiency) and democratization and self-government (which guarantee academic identity). The author points out that future reform or amendment of the provisions should ensure transparent relations between the rector and other university bodies and promote academic dialogue and broader academic participation by involving members of the academic community in important decision-making processes.